POST-COVID-19 HERITAGE TOURISM MANAGEMENT AT THE GEDONG ARCA MUSEUM IN BEDULU VILLAGE, BLAHBATUH DISTRICT, GIANYAR REGENCY - Ni Komang Tri Artiningsih; Ni Komang Sudarningsih; Astrid Krisdayanthi; Ketut Sumadi; Made Ika Kusuma Dewi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Since 2019, when the COVID-19 pandemic struck Indonesia, the pandemic has also affected visitor numbers at the Gedong Arca Archaeological Museum. In 2019, the museum began experiencing a significant decline in visits. However, as the COVID-19 pandemic began to subside and the government officially lifted the PPKM (Community Activity Restrictions) policy in 2022, visitor numbers to the Gedong Arca Museum started to rise and have continued to increase ever since. Based on this background, the research problems addressed in this study are: (1) tourists’ perceptions of heritage tourism at the Gedong Arca Museum in Bedulu Village, Blahbatuh District, Gianyar Regency; (2) the management of heritage tourism at the Gedong Arca Museum in Bedulu Village, Blahbatuh District, Gianyar Regency in the post-COVID-19 pandemic period; and (3) the implications of heritage tourism management at the Gedong Arca Museum in Bedulu Village, Blahbatuh District, Gianyar Regency after the COVID-19 pandemic on tourists and the local community. This study uses a qualitative descriptive analysis method, employing two theoretical frameworks: tourism management theory and symbolic interactionism theory. Data were obtained through observation, in-depth interviews, documentation, and literature studies. The data were then analyzed using qualitative descriptive techniques. Based on the perceptions of both tourists and the local community, the existence of the Gedong Arca Museum is viewed positively, particularly in terms of its collections of historical artifacts, available facilities, and the quality of staff services. The museum's presence has had a broadly positive impact on both tourists and the local community, particularly in the aspects of religious and social life, environmental awareness, socio-cultural dynamics, and the local economy.